Letter from W. L. Huber to J. R. Miller, March 2, 1918 - Walter Leroy Huber, 1883-1960::::::author:::; Julia Morgan::::::author::: (1918)
Subject line of the letter reads: 'Temporary Office Building Union Iron Works.'